Understanding the molecular orientation growth on a nanometer scale and adjustable electron transition performance of a terpyridyl derivative under different external environments. Issue 17 (21st March 2019) - Wang, Hai-Yan; Kong, Lin; Zhu, Shu-Juan; Zhou, Hong-Ping; Yang, Jia-Xiang
Abstract : TD-DFT calculation is used to forecast the aggregation style of PYTPY under different external conditions and predict the related morphology and electron transition performance. Abstract : In this study, a terpyridyl derivative 2-(6-(pyridin-2-yl)-4-(4-(( E )-2-(pyridin-4-yl)-vinyl)phenyl)pyridin-2-yl)pyridine (abbreviated as PYTPY) has been designed and prepared with an A–π–A architecture (A = electron acceptor), whose spontaneous aggregation style can be triggered by different external conditions. Mathematical modelling through time dependent density functional theory (TD-DFT) provides a quantitative understanding of the equilibrium molecular geometries at the aggregated state between adjacent PYTPY molecules with addition of different additives, such as water, H +, and Ag + ions. The vertical electronic excitations and the related UV-vis absorbing character of PYTPY under different conditions were also forecasted, which was verified by the examined absorption spectra. Our method of calculating intermolecular interactions between adjacent molecules and predicting spontaneous aggregation style and absorption performance under an external environment is generally applicable to design and create other functional organic materials.